Targeting the Extra-Cellular Matrix—Tumor Cell Crosstalk for Anti-Cancer Therapy: Emerging Alternatives to Integrin Inhibitors - Lorusso, Girieca; Rüegg, Curzio; Kuonen, François (Frontiers in Oncology, 2020)
The extracellular matrix (ECM) is a complex network composed of a multitude of different macromolecules. ECM components typically provide a supportive structure to the tissue and engender positional information and crosstalk with neighboring cells in a dynamic reciprocal manner, thereby regulating tissue development and homeostasis. During tumor progression, tumor cells commonly modify and hijack the surrounding ECM to sustain anchorage-dependent growth and survival, guide migration, store pro-tumorigenic cell-derived molecules and present them to enhance receptor activation. Thereby, ECM potentially supports tumor progression at various steps from initiation, to local growth, invasion and systemic dissemination and ECM-tumor cells interactions have long been considered promising targets for cancer therapy. Integrins represent key surface receptors for the tumor cell to sense and interact with the ECM. Yet, attempts to therapeutically impinge on these interactions using integrin inhibitors have failed to deliver anticipated results, and integrin inhibitors are still missing in the emerging arsenal of drugs for targeted therapies. This paradox situation should urge the field to reconsider the role of integrins in cancer and their targeting, but also to envisage alternative strategies. Here, we review the therapeutic targets implicated in tumor cell adhesion to the ECM, whose inhibitors are currently in clinical trials and may offer alternatives to integrin inhibition.